PENDAMPINGAN PENINGKATAN PENGELOLAAN DAN BRANDING PANTI ASUHAN - Sukmana, Oman; Astutik, Juli; Nasrullah (Universitas Djuanda, 2022)
This Community Service Program (Pkm) activity is the second year of Pkm implementation. In this second year, PKM activities are focused on mentoring efforts to help the administrators of the Putri Aisyiyah Orphanage Malang in improving the management and branding of the Putri Aisyiyah Orphanage in Malang City. The PKM activity method uses four activity methods, namely activities: socialization, training, mentoring, and facility assistance. The socialization activity was carried out in order to increase understanding related to the substance of the Minister of Social Affairs Regulation No.30/HUK/2011 concerning the National Standard of Child Care for Child Welfare Institutions; Training activities in the form of social media management training and training on child care patterns; Mentoring activities related to the profile of the Orphanage; and facility assistance activities in the form of providing assistance for filling cabinets to store administrative documents. In general, the results of this PKM activity have a positive impact where the knowledge, abilities, and awareness of the administrators and managers of the Aisyiyah Women's Orphanage in Malang City have increased and improved.